QUALITY EVALUATION ON PROCESSED MELONS (CUCUMIS MELO L.)PACKAGED IN PROTECTIVE ATMOSPHERE - Nicolais, Valeria; Russo, Mariateresa; Barbieri, Giancarlo; Rastrelli, Luca (Emirates Journal of Food and Agriculture, 2011)
In the last years the interest in the minimally processed horticultural products has increased because of the elevated level of convenience that they assure and for their organoleptical and functional characteristics that are very close to those of fresh products. This research was finalized to the production of pre-sliced melons packaged in protective atmosphere. In particular, the comparison between the behaviour of two different cultivars (Harper and Proteo) was monitored for 10 days, by studying the effect of the composition of four different gaseous mixtures on the qualitative characteristics of the products (microbiological quality, relative humidity, colour, firmness and chemical parameters), selecting in this way the cultivar with the greater attitude to the packaging.